2018
DOI: 10.1002/app.46889
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory polymers for self‐folding via compression of thermoplastic sheets

Abstract: We report a simple method to strain, and thereby program, shape memory polymers by compressing planar thermoplastic sheets. This work is motivated by the limited number of commercially available prestrained polymer sheets; current examples include: Shrinky Dinks, Eastman's Embrace, and polyurethane shrink films. However, these commercial specimens limit the sample thickness, polymer composition, and amount of stored strain. We show here that melt pressing can strain thermoplastic sheets over a range of thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The folding dihedral angle of a PMMA film could reach up to 180°, capable of enduring a weight of 9 kg. Hubbard et al 82 reported a cube with a thickness up to 12 mm via similar hinge and heating means, confirming the feasibility of this approach.…”
Section: Applicationsmentioning
confidence: 67%
See 1 more Smart Citation
“…The folding dihedral angle of a PMMA film could reach up to 180°, capable of enduring a weight of 9 kg. Hubbard et al 82 reported a cube with a thickness up to 12 mm via similar hinge and heating means, confirming the feasibility of this approach.…”
Section: Applicationsmentioning
confidence: 67%
“…6d(iii) . Amber et al 82 also adopted IR light to control the folding angle of a PS sheet with a thickness of 1 mm by patterning ink in hinge regions.…”
Section: Applicationsmentioning
confidence: 99%
“…Previously, polymer sheets have been folded using various methods, including light, , microwaves, lasers, magnetism, and heat. These methods can create multiple 3D shapes such as cubes, pyramids, and curvilinear objects . Many of these approaches to self-folding approaches use strain recovery gradients through the thickness of a single sheet of shape memory polymer .…”
Section: Introductionmentioning
confidence: 99%
“…This creates a shape‐memory effect in the processed plastic, which gives stretched polystyrene molecules more leeway when they are heated and softened again, and they tend to return to their more twisted, shrunken state before stretching. The film, stretched in both directions, contracts more evenly, so that after some magical distortions, the film eventually returns to a nearly flat state, without any visible distortion of the pattern . In 2008, Chen et al used Shrinky Dinks to create tiny structures for microfluidics applications in fields like stem cell research .…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Chen et al used Shrinky Dinks to create tiny structures for microfluidics applications in fields like stem cell research . TSP has since been used in both microfluidic and micro/nanodevice manufacturing . TSP can shrink to different degrees according to different heating temperatures and form 3D folds after shrinkage.…”
Section: Introductionmentioning
confidence: 99%